PENGEMBANGAN MODUL AJAR DENGAN MODEL KOOPERATIF TIPE JIGSAW BERBANTUAN LKPD INTERAKTIF UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF PESERTA DIDIK KELAS V SD - Anindi Putri, Mellyana; Widi Winarni, Endang; Muktadir, Abdul (UNIB Press, 2025)
The aim of this research is to develop a teaching module assisted by interactive LKPD on the water cycle with a cooperative jigsaw type model to improve cognitive learning outcomes. The type of research used is Research and Development (R&D) research using the ADDIE model. The type of data used is quantitative and qualitative data. Based on the results of this research, it was found that the application of teaching modules with a cooperative jigsaw type model assisted by interactive LKPD improved students' cognitive learning outcomes. This is shown by the results of the pretest and posttest assessments with an average score for C4 86% in the effective category, C5 76% in the quite effective category and C6 95% in the effective category. the application of science and science learning with teaching modules based on the jigsaw type cooperative model assisted by interactive LKPD significantly improves cognitive learning outcomes.